Association of depression phenotypes and antidepressant treatment with mortality due to cancer and other causes: a community-based cohort study - Vilalta-Lacarra, Anna; Vilalta-Franch, Joan; Serrano-Sarbosa, Domènec; Martí-Lluch, Ruth; Marrugat, Jaume; Garre-Olmo, Josep (Frontiers in Psychology, 2023)
Objective This study aimed to assess the association of somatic depressive symptoms (SDS), cognitive/emotional depressive symptoms (C-EDS), and antidepressant treatment on mortality due to cancer and other causes in a community cohort. Methods A community-based sample recruited in 1995, 2000, and 2005 aged between 35 and 75 years was examined in two waves and followed for a median of 6.7 years. SDS and C-EDS phenotypes were assessed using the Patient Health Questionnaire-9. Medication used by participants was collected. Deaths and their causes were registered during follow-up. Cox proportional hazard models stratified by sex were performed to determine the association between depressive phenotypes and mortality. Results The cohort consisted of 5,646 individuals (53.9% women) with a mean age of 64 years (SD = 11.89). During the follow-up, 392 deaths were recorded, of which 27.8% were due to cancer. C-EDS phenotype was associated with an increased risk of cancer mortality in both men (HR = 2.23; 95% CI = 1.11–4.44) and women (HR = 3.69; 95% CI = 1.69–8.09), and SDS was significantly associated with non-cancer mortality in men (HR = 2.16; 95 CI % = 1.46–3.18). Selective serotonin reuptake inhibitors (SSRIs) were significantly associated with both cancer (HR = 2.78; 95% CI = 1.10–6.98) and non-cancer mortality (HR = 2.94; 95% CI = 1.76–4.90) only in the male population. Conclusion C-EDS phenotype was related to an increased risk of cancer mortality at 6 years. In addition, the use of SSRIs in the male population was associated with cancer and all-cause mortality.